Soil nutrient availability affects tundra plant community composition and plant–vole interactions - Nicole Williamson; Matthew Suchocki; Laura Gough (Arctic, Antarctic, and Alpine Research)
Climate change in the Arctic is predicted to drastically alter carbon and nutrient pools, plant communities, and plant–animal interactions. We examined how four levels of long-term (16 years) nutrient addition in moist acidic tundra affected plant community structure and the abundance of Eriophorum vaginatum, the preferred forage for tundra voles (Microtus oeconomus). We also explored how simulated press and pulse herbivory for four years affected Eriophorum at these different nutrient levels. Shifts in plant community structure, reductions in species diversity and richness, and decreased Eriophorum abundance were pronounced at the highest levels of nutrient addition. Eriophorum abundance was negatively correlated with deciduous shrub abundance, likely caused by light limitation in fertilized plots. Added nutrients generally increased Eriophorum leaf length, but effects varied among years and simulated herbivory treatments. After being clipped once, Eriophorum leaves regrew in fertilized plots to the same length as leaves that had not been clipped, demonstrating recovery. Our results show how interannual variation in plant growth and animal activity might exacerbate or dampen responses over multiple years. Changes to plant community composition and plant–vole interactions associated with increased soil nutrients resulting from warming could have cascading impacts on arctic ecosystems and carbon cycling.